Arbajahan Ward Participatory Rangeland Resource Mapping Report - Mukalo, Irene Aloo; Akivaga, Allan (International Livestock Research Institute, 2023)
A report of the participatory rangeland resource mapping as a contribution to the implementation of participatory rangeland management (PRM) in Arbajahan ward, Wajir West, Kenya. Undertaken as a contribution to the AICCRA project.